Assessment of Competency Based on Dicotomic Scoring to Diagnose Students 'Skills in Vocational Learning in Vocational Schools - Wahid Munawar (Universitas Ahmad Dahlan, 2021)
Assessment of competency in schools is carried out by teachers using conventional tests, consists of multiple choice tests, essay tests, and skills tests using open scoring competency tests based on the teacher's principle of